2017
DOI: 10.1371/journal.pone.0170104
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index with Timing of Death during Tuberculosis Treatment

Abstract: BackgroundThe association between body mass index and mortality in patients with tuberculosis has not been extensively studied, and the existing evidence is inconsistent. This study aimed to investigate the impact of body mass index on timing of death in patients with tuberculosis.MethodsAll Taiwanese adults with tuberculosis in Taipei, Taiwan, were included in a retrospective cohort study in 2011–2012. Multinomial logistic regression was used to evaluate the association between body mass index and timing of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 19 publications
4
24
1
1
Order By: Relevance
“…All patients who died presented with a poor clinical condition at diagnosis. Severe underweight was an important predictor of mortality, consistent with findings from other settings [25,26]. We speculate that reducing the delay in treatment initiation will decrease mortality in the future [27].…”
Section: Discussionsupporting
confidence: 88%
“…All patients who died presented with a poor clinical condition at diagnosis. Severe underweight was an important predictor of mortality, consistent with findings from other settings [25,26]. We speculate that reducing the delay in treatment initiation will decrease mortality in the future [27].…”
Section: Discussionsupporting
confidence: 88%
“…We found that deaths were more likely among TB patients with HIV or undernutrition, which is consistent with the literature [22,23,45]. In contrast, DM was not associated with higher deaths, a finding consistent with our previous studies in Mexico, but not with reports from other populations [9,[46][47][48].…”
Section: Epidemiology and Infectionsupporting
confidence: 92%
“…The association of BMI with TB outcome was inconsistent in previous reports ( 4 , 7 12 ) . Four studies found that lower BMI was significantly associated with a higher risk of mortality among TB patients ( 8 10 , 12 ) , with one study reporting that greater BMI (per unit increase) was significantly associated with a lower risk of mortality ( 8 ) . In contrast, another two studies found no differences in the risk of mortality based on BMI (<18·5 v .…”
Section: Discussionmentioning
confidence: 78%
“…Although many studies have evaluated the risk factors for mortality in TB patients ( 6 ) , the association between BMI and mortality in this population has not been studied extensively, and the existing evidence is inconsistent ( 4 , 7 12 ) . Some studies reported that lower BMI was significantly associated with a higher risk of mortality among TB patients ( 7 10 , 12 ) , whereas another two found no such an association ( 4 , 11 ) . Moreover, one study found that overweight was a protective factor for mortality among TB patients ( 7 ) .…”
mentioning
confidence: 99%